2016
DOI: 10.1002/advs.201600254
|View full text |Cite
|
Sign up to set email alerts
|

PLGA‐PNIPAM Microspheres Loaded with the Gastrointestinal Nutrient NaB Ameliorate Cardiac Dysfunction by Activating Sirt3 in Acute Myocardial Infarction

Abstract: Acute myocardial infarction (AMI) is the death of cardiomyocytes caused by a lack of energy due to ischemia. Nutrients supplied by the blood are the main source of cellular energy for cardiomyocytes. Sodium butyrate (NaB), a gastrointestinal nutrient, is a short‐chain fatty acid (butyric acid) that may act as an energy source in AMI therapy. Poly(lactic‐co‐glycolic acid)‐Poly (N‐isopropylacrylamide) microspheres loaded with NaB (PP‐N) are synthesized to prolong the release of NaB and are injected into ischemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…AMI is a major cause of morbidity and mortality worldwide and needs to be addressed urgently [ 12 ]. Apoptosis and necrosis are 2 pivotal events of AMI, which are known to play important roles during the process [ 13 , 14 ]. Myocardial apoptosis is followed by necrosis, which occurs during sustained and severe ischemia, and it is an unregulated irreversible response to a fatal challenge which usually involves myocardial pump failure [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…AMI is a major cause of morbidity and mortality worldwide and needs to be addressed urgently [ 12 ]. Apoptosis and necrosis are 2 pivotal events of AMI, which are known to play important roles during the process [ 13 , 14 ]. Myocardial apoptosis is followed by necrosis, which occurs during sustained and severe ischemia, and it is an unregulated irreversible response to a fatal challenge which usually involves myocardial pump failure [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased acetylation of the ETC complexes correlates with a reduction in catalytic activity, impaired mitochondrial oxidative phosphorylation and consequently compromised contractile function of the heart. Therefore, approaches that upregulate and/or maintain SIRT3 expression and activity may represent a promising therapeutic strategy to treat or prevent cardiac dysfunction in the setting of MI [ 41 , 43 , 44 ]. In agreement with these reports, the current study demonstrated that the preserved SIRT3 activity in both sEH null mice or t AUCB pre-treated females subjected to MI correlates with enhanced cardiac contractile function compared to WT counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, netrin‐1‐modified small‐diameter TEBVs can get early inflammation resolution, which contributes to homing EPCs survival and quick endothelialization. Additionally, patients who need small‐diameter TEBVs often have the disease like diabetes or atherosclerosis, so we need further study the inflammatory condition and resolution ways of small‐diameter TEBVs in these disease state.…”
Section: Discussionmentioning
confidence: 99%